2021
DOI: 10.1021/acs.energyfuels.1c02110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carburization Conditions on the Activity of Molybdenum Carbide-Supported Catalysts Promoted by Nickel for the Dry Reforming of Methane

Abstract: The effect of the carburization temperature on the performance of nickelpromoted molybdenum carbides supported on γ-alumina and silicon carbide as catalysts in dry methane reforming at 800 °C was evaluated. The precursor oxides were synthesized via incipient wetness impregnation and carburized at 700, 750, and 800 °C employing temperatureprogrammed carburization. The effect of the carburization temperature was more evident for alumina-supported catalysts as a certain excess of carbon on the surface was needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
(132 reference statements)
0
13
0
Order By: Relevance
“…In the literature, there are multiple synthetic routes to prepare metal carbide nanocrystals including high temperature decomposition routes of molecular precursors, ,, carburization of metals and metal oxides, , and the recent demonstration of the thermal conversion of a metal organic framework or Prussian blue analogue (PBA) as single source precursors to the desired carbide. , While the use of high temperature M­(CO) 6 reactions to produce metal carbide precatalysts is reasonable in the laboratory, ,,, a synthetic route utilizing a single source precursor would be advantageous in the development of scalable and sustainable synthesis for industrial applications . PBAs can be converted to carbides and metals via calcining powders or solvothermally. , Researchers have shown pure phase carbides are isolable in Ni and Fe, but the isolated particles are insoluble and embedded in a carbonaceous layer. , …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are multiple synthetic routes to prepare metal carbide nanocrystals including high temperature decomposition routes of molecular precursors, ,, carburization of metals and metal oxides, , and the recent demonstration of the thermal conversion of a metal organic framework or Prussian blue analogue (PBA) as single source precursors to the desired carbide. , While the use of high temperature M­(CO) 6 reactions to produce metal carbide precatalysts is reasonable in the laboratory, ,,, a synthetic route utilizing a single source precursor would be advantageous in the development of scalable and sustainable synthesis for industrial applications . PBAs can be converted to carbides and metals via calcining powders or solvothermally. , Researchers have shown pure phase carbides are isolable in Ni and Fe, but the isolated particles are insoluble and embedded in a carbonaceous layer. , …”
Section: Introductionmentioning
confidence: 99%
“…Conditions: T = 1273 K, CH 4 /CO 2 = 1. Reprinted with permission from ref . Copyright 2021, American Chemical Society.…”
Section: Design Strategies Synthesis Approaches and Mechanisms Of Ni-...mentioning
confidence: 99%
“…Silva et al investigated the effects of carburization temperature on MDR performance and carbon deposition over the NiMoC x catalysts supported on γ-Al 2 O 3 and SiC (Figure II) . The catalysts were prepared by incipient impregnation and were carburized at temperatures from 973 to 1073 K. With the increase of the carburization temperatures, more carbon depositions were observed on the surface of the NiMoC x catalysts.…”
Section: Design Strategies Synthesis Approaches and Mechanisms Of Ni-...mentioning
confidence: 99%
See 1 more Smart Citation
“…247 It has been shown that Ni− Mo 2 C catalysts are neither deactivated by oxidation nor by carbon deposition as long as there is a sufficient carbon value on the surface. 251 The incomplete carbonization of Mo oxide and/or Ni oxide species in the low-temperature carbonization catalyst leads to the gradual transformation of them into highly active carbonized species or metal Ni species, resulting in the gradual increase of the H 2 formation rate and CH 4 conversion. 252 The results of Shi 250 and Cheng 253 et al have…”
mentioning
confidence: 99%